A new type of pH-sensitive phospholipid. Issue 50 (13th December 2017) - Zhan, Li; Chang, Shuyuan; Liu, Ting; Yu, Shanbao; Li, Hui; Lu, Minjie; Zhu, Yong; Luo, Yu; Yu, Jiahui; Yang, Fan; Tang, Jie
Graphical abstract: Highlights: A new type of pH-sensitive phospholipids with an acetal as the acid-labile moiety. This lipid was prepared by an eight-step synthesis via a latentiation strategy. This liposome could release its contents under mildly acidic conditions. This type of phospholipids was low toxic. Abstract: We describe the synthesis and characterization of a type of pH-sensitive pentaerythritol phospholipids, using a trialkoxybenzylidene acetal as the acid-labile moiety. This lipid was prepared by an eight-step synthesis via a latentiation strategy. Liposomes were prepared via the thin film extrusion method. The changes of liposomal sizes were measured by dynamic light scattering. Content release rates of the liposomes as a function of pH were monitored by using a calcein fluorescence dequenching assay. These results indicated that this new liposomal system was capable of releasing its contents under mildly acidic conditions. At last, in vitro cytotoxicity was assayed against three cell lines, suggesting this type of phospholipids was low toxic.